2021
DOI: 10.1089/scd.2020.0189
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Maturation of Human Pluripotent Stem Cell-Derived Renal Microtissue by Incorporation of Endothelial and Mesenchymal Cells

Abstract: Directed differentiation of human pluripotent stem cells (hPSCs) uses a growing number of small molecules and growth factors required for in vitro generation of renal lineage cells. Although current protocols are relatively inefficient or expensive. The first objective of the present work was to establish a new differentiation protocol for generating renal precursors. We sought to determine if inducer of definitive endoderm 1 (IDE1), a cost-effective small molecule, can be used to replace activin A. Gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…We assumed that the vascular structures that surrounded the BLOs through the highly porous 3D basket enhanced the maturation of the BLOs. Some studies have demonstrated the effect of in vivo and ex ovo vascularizations on the maturation of organoids or other tissues [33,34,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that the vascular structures that surrounded the BLOs through the highly porous 3D basket enhanced the maturation of the BLOs. Some studies have demonstrated the effect of in vivo and ex ovo vascularizations on the maturation of organoids or other tissues [33,34,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that the vascular structures that surrounded the BLOs through the highly porous 3D basket enhanced the maturation of the BLOs. Some studies have demonstrated the effect of in vivo and ex ovo vascularizations on the maturation of organoids or other tissues [ 33 , 34 , 50 , 51 , 52 ]. Here, we found that the transplanted BLOs could rapidly perform hepatic functions such as ALB secretion; in addition, ALT and AST levels in BLO-transplanted mice were significantly decreased compared to the sham group.…”
Section: Discussionmentioning
confidence: 99%
“…Several EPC populations play a key role in the formation of de novo vessels and nephrogenesis during kidney development (Munro et al 2017). There is extremely limited generation of ECs in the majority of current differentiation methods (0.3% or less of total cells) (Wu et al 2018;Khoshdel-rad et al 2021); many of these ECs have immature phenotypic characteristics. In addition, glomerular capillary formation is rare (Czerniecki et al 2018).…”
Section: Cellular Complexity During In Vitro Kidney Generationmentioning
confidence: 99%
“…Matrigel, has used as a reconstituted basement membrane derived from the Engelbroth Holm-Swarm (EHS) mouse sarcoma [149] that mimics mechanical and biochemical properties of ECM. This agent used to facilitate cellular self-organization, successful implantation of artifi cial tissue include kidney and bladder in patients [150]. Atala and colleagues showed that artifi cial bladders are composed of autologous cells (isolated from the patient) seeded on collagen or composite collagen and polyglycolic acid scaffolds.…”
Section: Kidney Ecm As a Natural Scaffoldmentioning
confidence: 99%
“…The using of decellularized biopsies of different regions of porcine kidneys including cortex, medulla, and papilla as the hydrogels and sheets of ECM showed that kidney stem cells had signifi cantly higher metabolic activity when cultured on papilla ECM [149]. In the intact ECM was observed potential to support proliferation of epithelial and endothelial cells, which consequently resulted in urine producing kidneys [150][151][152][153].…”
Section: Kidney Ecm As a Natural Scaffoldmentioning
confidence: 99%